Using Onboard-Produced Drinking Water to Achieve Ballast-Free Management - Lu, Kun-Tu; Lui, Hon-Kit; Chen, Chen-Tung Arthur; Liu, Li-Lian; Yang, Lei; Dong, Cheng-Di; Chen, Chiu-Wen (Sustainability, 2021)
Based on the International Convention for the Control and Management of Ships’ Ballast Water and Sediments (the Ballast Water Management Convention, or BWM Convention) of the International Maritime Organization, from 8 September 2017, all ships must have an approved Ballast Water Management Treatment System (BWTS) to prevent the invasion of alien species through the discharge of ballast. Generally speaking, the need for an approved BWTS is limited to large vessels, as they are too large or too expensive for small vessels to install. This study aims to propose a simple ballast-free approach for small vessels (e.g., tugs, workboats, research vessels) that require ballast to compensate for the weight loss of fuel when sailing. Our approach involves refitting the dedicated ballast tank of these small vessels to be drinking water tanks and filling the tanks with onboard-generated distilled or reverse osmosis water to adjust the stability of the ships. We assessed our approach using three vessels. Two ships using our proposed method were certified by the American Bureau of Shipping as containing no ballast water tank, and not being subject to the BWM Convention. This study provides an environmentally harmless, easy to use, and economical approach for small vessels to comply with the BWM Convention.